DESIGN OF DISSOLUTION STUDY PROTOCOL FOR PULMONARY DOSAGE FORMS: CRITERIA FOR SELECTION OF BIO-RELEVANT DISSOLUTION MEDIUM - DAS, SAUMYAJYOTI; SARKAR, PRASENJIT; BISWAS MAJEE, SUTAPA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Pulmonary dosage forms constitute an important route of drug delivery for systemic absorption of drugs in management of respiratory diseases as well as diseases such as diabetes, migraine, osteoporosis, and cancer. Performance of different pulmonary dosage forms is greatly influenced by aerodynamic particle size distribution of inhalable particles, spray pattern, fraction of dose actually deposited on pulmonary epithelium, dissolution of active pharmaceutical ingredient and ultimately absorption across pulmonary barriers. In vitro dissolution study should be designed to predict in vivo performance precisely, providing key information on bioavailability and establishing in vitro-in vivo correlation. To obtain meaningful data from dissolution study, focus should be on composition of dissolution medium, dissolution conditions and dissolution test apparatus. For pulmonary dosage forms, selection of physiologically relevant dissolution medium, mimicking lung fluid (LF) is a challenging task. Attempts are being made to develop bio-relevant dissolution medium to overcome the limitations associated with use of conventional media lacking lung surfactant proteins, or several salts normally present in pleural fluid. Use of simulated LFs can give a better understanding of the release mechanisms and possible in vivo behavior of pulmonary dosage forms thereby enhancing the predictive capability of the dissolution testing. In the review, efforts have been taken to provide comprehensive information on composition, physicochemical characteristics and functions of physiological LF, challenges associated with the design and development of dissolution study protocol for pulmonary dosage forms, criteria for selection of an appropriate bio-relevant dissolution medium, comparative study on various reported bio-relevant dissolution media and dissolution apparatuses employed for in vitro characterization of performance of pulmonary dosage forms.